Geology and Identification of Freshwater Sources Using Water Resistivity Survey in Landu Village, Rote Ndao, East Nusa Tenggara, Indonesia - Gunawan, Indra; Rudyawan, Alfend; Pamumpuni, Astyka; Handayani, Alfita Puspa; Hadiana, Meli; Sapiie, Benyamin; Febrianti, Adinda (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Located within the tectonically complex Banda Arc of eastern Indonesia, Landu Island, in Rote Ndao, East Nusa Tenggara provides a unique setting to investigate the relationship between arc-continent collision, karst development, and groundwater dynamics. The island is primarily underlain by Quaternary limestones, which form the principal aquifer system. Despite this hydrogeological potential, Landu faces acute freshwater shortages, particularly during the dry season. This study combines geological field mapping with a 1D electrical resistivity survey to characterize subsurface lithology, identify groundwater-bearing units, and assess the extent of seawater intrusion. The geological survey reveals slightly southward-tilted, fossiliferous limestones that exhibit clear evidence of karstification, indicating a history of tectonic uplift and surface water infiltration. A freshwater spring—currently the main source of potable water for the local population—was documented in the southeastern part of the island, with a total dissolved solids (TDS) concentration of 924 ppm, suggesting moderate water quality. Resistivity modeling identifies two potential aquifers: a shallow zone at depths of 5.2–17.2 m, and a more extensive, deeper reservoir between 35.1–92.1 m. The shallow aquifer shows lower resistivity values, indicative of possible saltwater mixing, which correlates with historical reports of failed boreholes in this zone. In contrast, the deeper aquifer exhibits higher resistivity signatures, suggesting better preservation of freshwater and greater potential for sustainable extraction. These findings highlight the critical influence of structural controls and karst processes on groundwater storage and quality. The study emphasizes the need for careful aquifer targeting and protection measures to prevent saltwater intrusion. Future work should focus on high-resolution geophysical imaging and long-term monitoring to support resilient water resource management on Landu Island.